PEMETAAN KUALITAS TANAH PADA LAHAN SAWAH DI KECAMATAN TUREN KABUPATEN MALANG - Christanti Agustina; Mochtar Lutfi Rayes; Evi Rosidha (Jurnal Tanah dan Sumberdaya Lahan, 2020)
Rice field management affects the physical, chemical and biological characteristics of the soil, as well as crop productivity. Efforts are needed to maintain soil conditions by measuring the soil quality index. The purpose of this study was to determine the characteristics of the soil as a reference pattern of soil quality distribution. This research was conducted in July - November 2019 in Turen District, Malang, using a free survey method based on the Land Map Unit. Soil samples were taken at a depth of 0-20 cm at each observation (24 points) and analyzed in the laboratory. The soil quality index was calculated according to limiting factors and scores relative to 10 soil quality indicators. Soil quality classes are grouped into 5 classes, i.e. (i) very good (<20), (ii) good (20-25), (iii) moderate (25-30), (iv) bad (30-40) and (v) very bad (> 40). The results showed that the soil in irrigated and rainfed rice fields had different limiting factor values in the levels of available-P, total-N, soil organic-C and microbial biomass-C which caused differences in soil quality. Crop productivity on the land showed differences based on land suitability classes resulting in S1 and S2 classes